Surface markers distinguishing mesenchymal stem cells from fibroblasts - KUNDROTAS, Gabrielis (Acta medica Lituanica, 2012)
Human mesenchymal stem cells (MSCs) are widely used for treatment of various diseases. Clinical applications require large quantities of MSCs, therefore these cells must be expanded in the culture system. It is believed that contamination of MSC cultures with fibroblasts may lead to the decrease of the stem cell differentiation potential. Moreover, such stem cell preparations are potentially unsafe to use for clinical applications since a few fibroblasts can become tumorigenic. Therefore, there is a need to separate MSCs from fibroblasts. However, studies show that MSCs and fibroblasts have much in common. These two types of cells share such properties as identical spindle-like morphology, plastic adherence and the same expression of most surface antigens. The aim of this review article is to analyze the literature on the similarities and differences between the MSCs and fibroblasts, particularly in the expression of cell surface markers in order to determine which could be used for quick separating of MSCs from fibroblasts. Interestingly, the results of recent studies suggest that the use of CD10, CD26, CD106, CD146 and ITGA11 could be helpful for the discrimination of MSCs from fibroblasts. Identification and elimination of fibroblasts from MSC cultures could improve the MSC yield and differentiation potential and also prevent possible tumor formation after MSC transplantation.